2021
DOI: 10.1002/ejoc.202100597
|View full text |Cite
|
Sign up to set email alerts
|

KO‐t‐Bu Catalyzed Thiolation of β‐(Hetero)arylethyl Ethers via MeOH Elimination/hydrothiolation

Abstract: Herein, we describe a KO‐t‐Bu catalyzed thiolation of β‐(hetero)arylethyl ethers through MeOH elimination to form (hetero)arylalkenes followed by anti‐Markovnikov hydrothiolation to afford linear thioethers. The system works well with a variety of β‐(hetero)arylethyl ethers, including electron‐deficient, electron‐neutral, electron‐rich, and branched substrates and a range of aliphatic and aromatic thiols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Shigeno and co‐workers have demonstrated the t BuOK catalyzed anti‐Markovnikov hydrothiolation of various aliphatic and aromatic β ‐(hetero) arylethyl ethers to produce the corresponding thioethers in good to excellent yields (Scheme 34). [29] In the preliminary investigation of the reaction, 20 mol% of t BuOK was found to be an effective catalyst and successfully employed for hydrothiolation reaction. The reaction conditions have been applied to diverse β ‐(hetero) arylethyl ethers using different aliphatic and aromatic thiols.…”
Section: Role Of Catalytic Amounts Of Alkali Metal (Li Na and K) Tert...mentioning
confidence: 99%
“…Shigeno and co‐workers have demonstrated the t BuOK catalyzed anti‐Markovnikov hydrothiolation of various aliphatic and aromatic β ‐(hetero) arylethyl ethers to produce the corresponding thioethers in good to excellent yields (Scheme 34). [29] In the preliminary investigation of the reaction, 20 mol% of t BuOK was found to be an effective catalyst and successfully employed for hydrothiolation reaction. The reaction conditions have been applied to diverse β ‐(hetero) arylethyl ethers using different aliphatic and aromatic thiols.…”
Section: Role Of Catalytic Amounts Of Alkali Metal (Li Na and K) Tert...mentioning
confidence: 99%
“…We have previously reported that the phosphazene t -Bu-P4 base catalyzes the nucleophilic aromatic substitution of methoxyarenes, whereby the C(sp 2 )–OMe bonds are substituted by alcohol, amine, and alkanenitrile pronucleophiles. 12,13 Herein, we report that this organic superbase catalyzes the demethylation of methoxyarenes in the presence of thiol and hexamethyldisilazane (HMDS) (Fig. 1c).…”
Section: Introductionmentioning
confidence: 96%
“…Nucleophiles with relatively acidic C­(sp) 3 –H bonds (p K a ≈ 18–25), such as aldehydes, malonic acids, nitroalkanes, and ketones can effectively undergo a deprotonative addition reaction with several electrophiles . Recently, the functionalization of weakly acidic C­(sp) 3 –H bonds (p K a > 30), such as esters, nitriles, amides and alkylazaarenes, catalyzed by the Brønsted base has also been developed by Pines, Knochel, Guan, Shigeno and Kondo, and Kobayashi. , …”
Section: Introductionmentioning
confidence: 99%